Comparison of SD Bioline Malaria Ag Pf/Pan and Acro Malaria P.f./P.v./Pan with Microscopy and Real Time PCR for the Diagnosis of Human Plasmodium Species - Marylin Madamet; Isabelle Fonta; Joel Mosnier; Nicolas Benoit; Rémy Amalvict; Sébastien Briolant; French National Reference Centre for Imported Malaria Study Group; Bruno Pradines (Diagnostics, 2024)
The early diagnosis of malaria is crucial to controlling morbidity and mortality. The World Health Organization (WHO) recommends diagnosing malaria either using light microscopy or a malaria rapid diagnostic test (RDT). Most RDTs use antibodies to detect two P. falciparum histidine-rich proteins named PfHRP2 and PfHRP3. However, false-negative results are known to occur due to the poor performance of RDTs depending on the species and the deletion of the Pfhrp2 and Pfhrp3 genes. This study evaluated new malaria RDTs for the detection of the human Plasmodium species. The Acro Malaria P.f./P.v./Pan Rapid Test Cassette allows the qualitative detection of parasite antigens, such as PfHRP2 specific to Plasmodium falciparum, PvLDH specific to Plasmodium vivax, and/or panLDH Plasmodium genus lactate dehydrogenase, in the blood of infected individuals. This RDT was assessed against 229 samples collected from imported malaria cases, mainly from Africa. The samples were previously diagnosed using light microscopy and RDT (SD Malaria Ag P.f./Pan, SD Bioline Alere Abbott), then confirmed using real time PCR. The two RDTs were evaluated using a comparison with real time PCR as the reference method, and their performances were compared with each other. Compared to SD RDT, the Acro RDT showed a better sensitivity to P. falciparum (96.8% vs. 89.8%), P. vivax (78.6% vs. 64.3%), P. ovale (73.7% vs. 5.3%), and P. malariae (20.0% vs. 0%). The respective specificities of the Acro RDT and SD RDT are 90.7% vs. 95.3% to P. falciparum, 100% to P. vivax, and 100% vs. 100% to Plasmodium genus. Therefore, Acro RDT showed better performance in the identification of P. ovale and low parasitaemia of P. falciparum. In addition, Acro RDT has the advantage of detecting PvLDH-specific antigens. The Acro Malaria RDT presents the benefits of detecting a P. falciparum antigen (PfHRP2) and a P. vivax antigen (PvLDH) with high sensitivity (96.8% and 73.7%, respectively) and specificity (90.7% and 100%, respectively). Acro Malaria P.f./P.v./Pan rapid diagnostic tests could be effectively used in endemic areas, especially when microscopic examination cannot be performed.